Significance of Agriculture in the Economic Structure and Economic Development of Transition Countries - Jelić, Sreten M.; Kolarević, Vukašin Ž. (Sociološki pregled, 2019)
In this paper, authors aim to show the significance of agriculture in the economic structure and economic development of transition countries. The role of agriculture is undoubtable in the economic development of transition countries particularly because agriculture represents an important branch of economy in former socialist systems, but also of the structural reform in agrarian sector. Special emphasis is placed on the analysis of indicators of significance for agriculture in economic structure and economic development of individual transition countries. The analysis includes transition countries of the EU, Western Balkan countries and the countries of the Commonwealth of Independent States. The analyzed data refers to the period from 1989 until today, with results created for shorter periods for comparison.